Association of Genetic Variants at TRPC6 With Chemotherapy-Related Heart Failure - Norton, Nadine; Crook, Julia E.; Wang, Liwei; Olson, Janet E.; Kachergus, Jennifer M.; Serie, Daniel J.; Necela, Brian M.; Borgman, Paul G.; Advani, Pooja P.; Ray, Jordan C.; Landolfo, Carolyn; Di Florio, Damian N.; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Our previous GWAS identified genetic variants at six novel loci that were associated with a decline in left ventricular ejection fraction (LVEF), p<1x10-5 in 1,191 early breast cancer patients from the N9831 clinical trial of chemotherapy plus trastuzumab. In this study we sought replication of these loci. Methods: We tested the top loci from the GWAS for association with chemotherapy-related heart failure (CRHF) using 26 CRHF cases from N9831 and 984 patients from the Mayo Clinic Biobank which included CRHF cases (N=12) and control groups of patients treated with anthracycline +/- trastuzumab without HF (N=282) and patients with HF that were never treated with anthracycline or trastuzumab (N=690). We further examined associated loci in the context of gene expression and rare coding variants using a TWAS approach in heart left ventricle and Sanger sequencing, respectively. Doxorubicin-induced apoptosis and cardiomyopathy was modelled in human iPSC-derived cardiomyocytes and endothelial cells and a mouse model, respectively, that were pre-treated with GsMTx-4, an inhibitor of TRPC6. Results: TRPC6 5’ flanking variant rs57242572-T was significantly more frequent in cases compared to controls, p=0.031, and rs61918162-T showed a trend for association, p=0.065. The rs61918162 T-allele was associated with higher TRPC6 expression in the heart left ventricle. We identified a single TRPC6 rare missense variant (rs767086724, N338S, prevalence 0.0025% in GnomAD) in one of 38 patients (2.6%) with CRHF. Pre-treatment of cardiomyocytes and endothelial cells with GsMTx4 significantly reduced doxorubicin-induced apoptosis. Similarly, mice treated with GsMTx4 had significantly improved doxorubicin-induced cardiac dysfunction Conclusions: Genetic variants that are associated with increased TRPC6 expression in the heart and rare TRPC6 missense variants may be clinically useful as risk factors for CRHF. GsMTx-4 may be a cardioprotective agent in patients with TRPC6 risk variants. Replication of the genetic associations in larger well characterized samples and functional studies are required.